2021
DOI: 10.3390/ijerph18031062
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Child and Adolescent Mental Health during the COVID-19 Pandemic in Ireland

Abstract: Mitigating the adverse physical health risks associated with COVID-19 has been a priority of public health incentives. Less attention has been placed on understanding the psychological factors related to the global pandemic, especially among vulnerable populations. This qualitative study sought to understand the experiences of children and adolescents during COVID-19. This study interviewed 48 families during the COVID-19 pandemic restrictions, and a national lockdown, to understand its impacts. The study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
220
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 34 publications
18
220
1
11
Order By: Relevance
“…A study of parents of 125 children with disabilities in the UK found that 61% of them reporting a reduction in physical activity levels and over 90% reported a negative impact on their children's mental health 250 . A qualitative study in Ireland came to a similar conclusion regarding increased mental health difficulties among children with Autistic Spectrum Disorder 251,252 . Patients fearful of acquiring COVID-19 infection have also been found to postpone medical care for their chronic problems 253 , leading to greater physical and psychological distress, while adding to the suffering of chronically ill patients 227,254,255 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 69%
“…A study of parents of 125 children with disabilities in the UK found that 61% of them reporting a reduction in physical activity levels and over 90% reported a negative impact on their children's mental health 250 . A qualitative study in Ireland came to a similar conclusion regarding increased mental health difficulties among children with Autistic Spectrum Disorder 251,252 . Patients fearful of acquiring COVID-19 infection have also been found to postpone medical care for their chronic problems 253 , leading to greater physical and psychological distress, while adding to the suffering of chronically ill patients 227,254,255 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 69%
“…Similar reflections have been identified among families in Australia, including being stressed and missing out on important social activities as well as disruption in routines and activities [ 37 ]. Children may be especially vulnerable during the COVID-19 pandemic as they are in critical periods of development and have limited control over their own circumstances or decision-making, impacting mental health [ 25 , 38 ]. CIM and physical activity are associated with the positive development and well-being of children and are often one of the main ways children and families form peer networks [ 9 , 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding perceived and experienced impacts of SAH, many parents reported that being out of school had adverse psychological effects for their children (e.g. O'Sullivan et al 2021). From a student perspective, the most salient stressor of SAH was a loss of peer interaction and support and, for second-level students, an increase in school workload (e.g.…”
Section: Introductionmentioning
confidence: 99%